Gobierno abierto en la alcaldía de machala: fortalezas, debilidades y desafíos. - Ruiz Cajamarca, Jonathan Bryan (Machala, 2019)
This research work is focused on the study on Open Government, a term that for some years has been awakening the interest of several countries to seek new ways of doing government, building trust between public management and citizenship in an ethical, responsible manner and always subject to social control. Open Government (GA) officially implemented in Ecuador since July 2018 has motivated different local governments to transparent their efforts and to involve citizens in decision making. In this context, this research is presented with the objective of establishing the importance of the implementation of open government initiatives in the Machala mayor's office, determining the possible challenges it faces. For this, an evaluation of compliance with basic dimensions of open government was carried out such as: citizen participation, transparency and accountability in said institution, to corroborate that first evaluation, an analysis was made on the knowledge and use of government open both by the public and by the internal public of the mayor's office, specifically departments that handle public information dissemination and socialization processes. On the other hand, it was necessary to consider the criteria of experts, both from the point of view of the institution so that the degree of interest that the mayor has to continue with these policies and how much they are willing to potentiate these information transparency processes can be established and data, as well as from the point of view of government policies to understand the current and real landscape of open government in Ecuador. Among the results obtained, it was found that the mayor's office of Machala, in front of its recent administration, is in a process of readjustment and evaluation of all its functions, despite this, it was determined that the internal public of said institution lacks of sufficient information on open government, fundamental pillars, objectives or strategies, in spite of that, it is possible to demonstrate their interest in strengthening their knowledge, analyzing new strategies under professional advice, and potentiating citizen participation in their decision-making and management processes . Thus, it could also be determined that despite the fact that the mayor's office of Machala considers new technologies in its transparency and accountability processes, according to the bibliography consulted, they do not fully comply with the basic categories of open government, reducing the effectiveness of their services offered to citizens through its web portal; information verified through surveys to determine the level of knowledge of the citizenship about the information offered by the mayor's office through its dissemination channels, specifically its web portal. Thus reaching the following conclusions, the role of open government in municipal government institutions allows establishing a close link between society and these institutions, in the mayor's office of Machala, who faces a process of transition of administrations, will significantly generate more interaction and citizen participation in the decision-making process that, at the end of the day, will show a transparent government that will have as challenges the same fear, product of the same ignorance, both from the authorities that doubt to transparent institutional and political information, and also by the citizens that He fears taking responsibility if he intervenes in the processes. The lack of interest of citizens with respect to public policies or municipal political information, influences the execution of strategies by the mayor's office to use new technologies in transparency and accountability processes. And to conclude, the mayor's office of Machala, despite presenting a novel administration of less than a year, presents a lot of interest in improving the processes of transparency of public information, perhaps its weaknesses in lack of training and knowledge on this issue on servers municipal in different related departments, has encouraged the institution to promote knowledge about this initiative.
El presente trabajo de investigación está enfocado en el estudio sobre Gobierno Abierto, término que desde hace algunos años ha venido despertando el interés de varios países por buscar nueva forma de hacer gobierno, sembrando confianza entre la gestión pública y la ciudadanía de manera ética, responsable y siempre sujeta al control social. Gobierno Abierto (GA) implementado de manera oficial en el Ecuador desde julio el 2018 ha motivado a diferentes gobiernos locales a transparentar sus gestiones y a hacer partícipes a la ciudadanía en la toma de decisiones. En este contexto se plantea la presente investigación con el objetivo de establecer la importancia de la implementación de iniciativas de gobierno abierto en la alcandía de Machala, determinando los posibles desafíos a los que se enfrenta. Para esto se realizó una evaluación del cumplimiento de dimensiones básicas de gobierno abierto como lo son: la participación ciudadana, la transparencia y la rendición de cuentas en dicha institución, para corroborar esa primera evaluación, se hizo un análisis sobre el conocimiento y uso de gobierno abierto tanto por parte de la ciudadanía como por parte del público interno de la alcaldía, específicamente departamentos que manejen procesos de difusión y socialización de información pública. Por otro lado, fue necesario considerar el criterio de expertos, tanto desde el punto de vista de la institución para que pueda establecerse el grado de interés que tiene la alcaldía por continuar con estas políticas y cuánto están dispuesto a potencializar estos procesos de transparencia de información y datos, así como también desde el punto de vista de las políticas de gobierno para comprender el panorama actual y real de gobierno abierto en Ecuador. Entre los resultados que se obtuvieron se encontró que la alcaldía de Machala, frente a su reciente administración, se encuentra en un proceso de reajuste y evaluación de todas sus funciones, a pesar de ello, se pudo determinar que el público interno de dicha institución carece de información suficiente sobre gobierno abierto, pilares fundamentales, objetivos o estrategias, a pesar de aquello, se puede evidenciar su interés por fortalecer su conocimiento, analizar nuevas estrategias bajo asesoramiento profesional, y potencializar la participación ciudadana en sus procesos de toma de decisiones y gestión. Así también se pudo determinar que a pesar que la alcaldía de Machala, considera las nuevas tecnologías en sus procesos de transparencia y rendición de cuenta, según bibliografía consultada no cumplen en su totalidad con las categorías bases del gobierno abierto, disminuyendo la eficacia de sus servicios ofrecidos a la ciudadanía a través de su portal web; información contrastada mediante encuestas para determinar el nivel de conocimiento de la ciudadanía sobre la información que ofrece la alcaldía mediante sus canales de difusión, específicamente su portal web. Llegando así a las siguientes conclusiones, la función del gobierno abierto en las instituciones gubernamentales municipales permite establecer un estrecho vínculo entre la sociedad y dichas instituciones, en la alcaldía de Machala, quien enfrenta un proceso de transición de administraciones, permitirá significativamente generar mayor interacción y participación ciudadana en la toma de decisiones que al final de cuentas evidenciará un gobierno transparente que tendrá como desafíos el mismo miedo, producto del mismo desconocimiento, tanto desde las autoridades que dudan transparentar información institucional y política, y así también por parte de la ciudadanía que teme asumir responsabilidades si interviene en los procesos. La falta de interés de la ciudadanía con respecto a las políticas públicas o información política municipal, influye en la ejecución de estrategias por parte de la alcaldía para usar las nuevas tecnologías en procesos de transparencia y rendición de cuenta. Y para concluir, la alcaldía de Machala, a pesar de presentar una administración novel de menos de un año, presenta mucho interés en mejorar los procesos de transparencia de información pública, quizás sus debilidades en falta de capacitación y conocimiento sobre este tema en los servidores municipales en distintos departamentos relacionados, ha incentivado a la institución a promover el conocimiento sobre dicha iniciativa.
Keywords: GOBIERNO ABIERTO; PARTICIPACION CIUDADANA; TRANSPARENCIA; COLABORACION